Implementation of Accounting Information System For Raw Material Control - Adriani Lande; Kartim; Septyana Prasetianingrum; Sahrul Ponto; Muhammad Ridhwansyah Pasolo (Jurnal Mantik, 2022)
The use of information systems is currently required by the business to support business operations so that the implementation of various processes, including the accounting system for controlling raw materials, can go smoothly and be focused on achieving the business's objectives. The control of a company's raw material inventory is related to one aspect of the accounting system. Inventory control must be taken into account because it directly affects the costs that the business must bear as a result of inventory. As a result, the inventory currently in place must be balanced with needs, as raw material inventory is the primary factor in the business that supports a productive production process. With the help of activities and procedures related to accounting information systems, raw material inventory control systems, and company sales targets, this study seeks to analyze the function of accounting information systems in controlling raw material inventory. Along with resolving issues with the company's financial transaction data recording, a system that can generate thorough raw material recording reports must be developed in order to improve the company's raw material recording. The design of the raw material control accounting information system has been successfully made in accordance with the company's business processes and user needs analysis, as shown by the results of system development using the System Development Life Cycle (SDLC) method, so that system testing with blackbox testing demonstrates the system can function as expected.